The Million Farmers School: An evaluation of its impact on farmers’ agricultural knowledge in Uttar Pradesh, India - Kumar, Anjani; Verma, Smriti; Prasad, Amit Mohan; Kishore, Avinash; Saroj, Sunil (International Food Policy Research Institute, 2019)
The Million Farmers School (MFS) is an innovative extension program initiated by the Department of Agriculture in the state of Uttar Pradesh, India, in 2017. Twice in a year, the department deploys its entire extension machinery to organize nearly 15,000 training programs for about a million farmers across all districts of the state. Unlike traditional extension services, MFS integrates various facets of agricultural knowledge into a packaged product and delivers through village-level trainings where printed material on the topics of training are also distributed among participants. This study presents early findings of a process evaluation, involving assessments of program design, implementation strategies, and estimation of benefits from program participation. In addition to consultation with public officials and community organizations, a state-level representative survey was conducted on a sample of both participating and non-participating households. The early results based on matching and instrumental variable methods—suggest that knowledge outcomes are significantly better among participants vis-à-vis non-participants. The results are robust to different model specifications. The study also qualitatively assesses various aspects of the program’s design and implementation, highlighting the constraints and challenges it faces and offers implementation advice for greater efficacy in its future course.